Heat transfer enhancement of wall with a near wall cylinder in a channel at low and middle Reynolds number ranges. (November 2020) - Xu, Hui; Cai, Yixi; Xi, Guannan
This paper investigated the flow performance around a near-wall cylinder and its effect on heat transfer enhancement in the laminar and early transitional flow region. The numerical model is resolved by finite volume method through FORTRAN code. The results show that the flow field becomes a transitional flow state when Re = 100 due to the insertion of a cylinder. In the transitional flow sate, the heat transfer enhancement is regional, mainly concentrating in the region of –2 ≤ x/D ≤ 10, and the region increases with the increase of Re ; There are three or four peaks in the distribution of instantaneous local Nusselt number. The first peak is caused by the acceleration of the fluid between the cylinder and the bottom wall. The other peaks are caused by the interaction between the cylinder wake and the bottom wall boundary layer. The vortical structure induced by the periodic instability of the fluid in the transitional flow is the main factor for explaining the local heat transfer enhancement of the cylinder downstream wall. Re has a direct impact on the vortical structure in the flow field. The greater Re, the greater the heat transfer enhancement of the cylinder downstream wall. Under the same blocking ratio of D/H, the greater Re, the smaller the optimal clearance ratio of C/D . The guidelines are suggested for the design on heat dissipation of electronic equipment.